PERSPEKTIF TEORETIS PENDIDIKAN ISLAM: Studi Komparatif terhadap Terma Tarbiyyah, Ta’dīb, dan Ta‘līm - Muljono Damopolii (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
The term of Islamic education has been concerned seriously by the Moslem scholars. It is proven that many theories of Islamic education were made either by local authors or international ones. The theoretical framework of Islamic education has been related to the terms of tarbiyyah, ta’dīb, and ta‘līm. There are many philosophical reasons stated by scholars in supporting to use one of the terms. For example, the term of tarbiyyah is regarded with the representative term of Islamic education than the terms of ta’dīb and ta‘līm.